Generation of Foxo3‐targeted Mice by Injection of mRNAs Encoding Transcription Activator‐like Effector Nucleases (TALENs) into Zygotes. Issue 3 (20th March 2015) - Zhu, P; Liu, Q; Liu, S; Su, X; Feng, W; Lei, X; Liu, J; Cui, K; Huang, B; Shi, D
Contents: In this study, for exploring the mechanism of forkhead box O3(Foxo3) participating in regulation of the activation of primordial oocytes, Foxo3‐targeted mice were generated by injection of mRNAs encoding transcription activator‐like effector nucleases (TALENs) into mouse zygotes. The TALEN sites were designed with high conservative homologous region among pig, bovine, buffalo and mouse by commercial bio‐companies. The TALENs mutagenic non‐homologous end‐joining (NHEJ) repair activity were determined to be 31.3% in human embryonic kidney 293T (HEK‐293T) cells by dual luciferase reporter assay system. Then, we firstly injected TALEN‐mRNAs into the cytoplasm of mouse zygotes by micromanipulation, and four of 48 mouse blastocysts were identified as mutation by sequencing. Subsequently, by the method of TALEN‐mRNAs injected into the zygotes with pronucleus micromanipulation technique, we obtained seven Foxo3 mutants of 20 FVB/NJ backgrounds mice which were Foxo3‐independent alleles with frameshift and deletion mutations. It was very interesting that all seven were heterozygous mutants (Foxo3 −/+ ), and the gene mutagenesis rates of the mice reached 35%. The five Foxo3 mutant females were all infertile in the following 6 months after birth. The histological examination results showed that there were rare primordial follicles and primary follicles in the ovary of Foxo3 mutant compared to that of wide‐type female mice. Moreover, one of two mutant males was subfertile and another was fertile normally. Those results suggested that the mutant of Foxo3 severely affected the fertile ability of female and perhaps male in some degree; furthermore, an even more efficient TALENs‐based gene mutation method has been established to be poised to revolutionize the study of mouse and other species genetics.